If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2u + 10 = 17 Reorder the terms: 10 + 2u = 17 Solving 10 + 2u = 17 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 2u = 17 + -10 Combine like terms: 10 + -10 = 0 0 + 2u = 17 + -10 2u = 17 + -10 Combine like terms: 17 + -10 = 7 2u = 7 Divide each side by '2'. u = 3.5 Simplifying u = 3.5
| 2(x-7)-12=6 | | 7+2(x+5)=49 | | 3(x+4)+7=61 | | 3+9q=5+8q | | -3(x-5)=27 | | -4(x+6)=96 | | 2(x-14)=66 | | 5(-3)-15=-4(-3)+12 | | 5(x+6)=120 | | 5(3)-15=-4(3)+12 | | 3(x+2)=24 | | 2(4p-2)=-24 | | (x+4)(x+2)=x-(1-x^2) | | 1/2(6-3)=5/2 | | -k^2+11k-15=3 | | 18.9=2.1 | | (2-b)(2+5)-11=24 | | 7-x-x=-1 | | 27b=59 | | 7x=8+6 | | 4x+5=x-2 | | (a+1)(15-2)+3=42 | | 2x+70-5x=31 | | =(3x^3y^4)(4xy^5) | | 6x^2+17x-12=0 | | 2u-3= | | 3+5x=39+6 | | 23-12(1-9)=12 | | 3=4-1(x+1) | | 80x+8=76 | | 2x+26=9x+4 | | 4*x+30=4.50*x |